The Use of CLIL Activities in Teaching English (Texas Journal of Multidisciplinary Studies, 2022)
This article is devoted to content and language integrated learning and the activities which is very useful to use in English classes. CLIL helps students discover and develop multiple skills, to improve their communication skills.